Sound evoked fos-like immunoreactivity in the big brown bat - Angeles Salles; Shirley Marino Lee; Cynthia F. Moss (IBRO Neuroscience Reports, 2022)
Most bat species have highly developed audio-vocal systems, which allow them to adjust the features of echolocation calls that are optimized for different sonar tasks, such as detecting, localizing, discriminating and tracking targets. Furthermore, bats can also produce a wide array of social calls to communicate with conspecifics. The acoustic properties of some social calls differ only subtly from echolocation calls, yet bats have the ability to distinguish them and reliably produce appropriate behavioral responses. Little is known about the underlying neural processes that enable the correct classification of bat social communication sounds. One approach to this question is to identify the brain regions that are involved in the processing of sounds that carry behavioral relevance. Here, we present preliminary data on neuronal activation, as measured by c-fos expression, in big brown bats (Eptesicus fuscus) exposed to either social calls, echolocation calls or kept in silence. We focused our investigation on five relevant brain areas; three within the canonical auditory pathway (auditory cortex, inferior colliculus and medial geniculate body) and two that are involved in the processing of emotive stimulus content (amygdala and nucleus accumbens). In this manuscript we report c-fos staining of the areas of interest after exposure to conspecific calls. We discuss future work designed to overcome experimental limitations and explore whether c-fos staining reveals anatomical segregation of neurons activated by echolocation and social call categories.